Assessment of undergraduate student knowledge, attitude, and practices towards COVID-19 in Debre Berhan University, Ethiopia. - Yared Asmare Aynalem; Tadess Yirga Akalu; Birhan Gebresellassie Gebregiorgis; Nigussie Tadesse Sharew; Hilina Ketema Assefa; Wondimeneh Shibabaw Shiferaw (PLoS ONE)
Background Novel coronavirus-2019 (COVID-19) is a highly infectious disease that has caused a global pandemic. As of July 2020, there were 8,475 confirmed cases of COVID-19 in Ethiopia, and a total of 52 cases and 1 death were reported in Debre Berhan where this study was conducted. Under these conditions, we sought to assess what undergraduate students at Debre Berhan University knew about COVID-19 and how it shaped their attitudes and practices regarding this disease. Objective The aim of the current study was to assess undergraduate student knowledge, attitudes and practices towards COVID-19 in Debre Berhan University, Ethiopia. Methods A cross-sectional survey was conducted from March 18-24, 2020 among undergraduate students at Debre Berhan University. A two-stage cluster sampling technique was employed with a total sample size of 634. Proportional allocation of samples was used to the randomly selected colleges, and a systematic random sampling technique was employed to recruit the students. The data were checked for completeness, coded, entered into Epi-Data VS 3.1, and then exported into STATA™ Version 14 software for analysis. Descriptive statistics were conducted. Binary logistic regression analyses were used to identify factors. Factors were selected with the entry method. Adjusted odds ratios (AORs) and their 95% confidence intervals (CIs) were used to assess the associations between variables and knowledge, attitude and practices (KAP). Results From a total of 546 included participants, more than half of them, 307 (57%) were males. Seventy-three percent of them heard about novel coronavirus from social media. In this study, 73.8% of the participants were knowledgeable, and their overall attitude was favorable. Approximately 71.4% correctly responded that the main clinical symptoms of COVID-19 are fever, fatigue, dry cough, and shortness of breath. Nearly half, 229 (42%) of the students approved that they had no concern of being infected with COVID-19. Moreover, most participants showed poor practices; more than half of the study subjects were not maintaining a physical distance. In multivariable analyses, people older than 25 years (AOR = 1.6, 95% CI; 1.2, 4.6) and those who lived in urban areas (AOR = 4.3, 95% CI; 2.6, 15.8) were significantly more knowledgeable about COVID-19. Furthermore, those students that have information about COVID-19 (AOR = 2.3, 95% CI; 1.6, 8.7) was significantly associated with the attitude undergraduate students had about COVID-19 as compared with its counterpart. Conclusion The undergraduate students at Debre Berhan University were moderately knowledgeable about COVID-19 and had an optimistic attitude towards its resolution. However, this optimism may lead to poor public health practices within this community. Therefore, greater efforts need to be made through more comprehensive and directed actions and awareness campaigns to increase the knowledge, attitude and practice of the students.